Measuring Climate Risks: A New Multidimensional Index for Global Vulnerability and Resilience - Heidi Edmonds; Johanna Fajardo-Gonzalez; Julie Lovell; C.A. Knox Lovell (Global Labor Organization (GLO), 2025)
As climate change intensifies, countries experience varying degrees of vulnerability and resilience that influence their capacity to withstand and recover from environmental, economic, and social shocks. This study introduces the Multidimensional Vulnerability and Lack of Resilience Index (MVLRI), a novel framework that goes beyond traditional vulnerability assessments by incorporating resilience as a critical component. The MVLRI synthesizes twenty-six key indicators across economic, environmental, and social dimensions, providing a comprehensive measure of how countries confront climate risks. Findings reveal that vulnerability and resilience are distinct yet complementary factors, each significantly contributing to the overall index. These contributions vary widely across countries, reflecting diverse climate risks and socioeconomic contexts. The importance of including resilience in policy frameworks is emphasized, as neglecting it could undermine the effectiveness of interventions aimed at reducing climate impacts. Furthermore, the MVLRI demonstrates strong correlations with institutional performance indicators, illustrating how governance, economic stability, and social equity shape a country's capacity to cope with climate adversity. By offering a multidimensional perspective, the MVLRI equips policymakers with a powerful tool to design targeted interventions that address both vulnerability and resilience. This approach enables more effective resource allocation and policy decisions, helping countries better anticipate, respond to, and recover from the growing threats posed by global climate change.
Keywords: Q54; Q56; C24; C43; C6; 330; climate change; vulnerability; resilience; composite index